PENGARUH KONSEP DIRI TERHADAP INTENSI MEMBELI PRODUK BERMEREK PADA REMAJA DI JAKARTA - Lydia Lydia; Devi Jatmika (Universitas Bunda Mulia, 2018)
Adolescence is generally focused on the physical appearance of an influence on the way they perceive themselves or are known by the term self-concept. Purchase intention each of individual is believed to be influenced by self- concept, because in it increased sense of self confidence. The purpose of this study was to assess the effect of self-concept to the intention to purchase a branded product in adolescents in Jakarta. This study uses quantitative methods with the type of causal comparative research. The study involved 158 adolescents who have been through the assessment stage of self-criticism with an age range of 15-21 years. Characteristics of the subjects in this study, namely young men and women, aged 15-21 yearsin Jakarta, and ever purchase a minimum of one kind of branded products. This research analyzed at the effect of self-concept on the purchase intention by using simple linear regression techniques. The analysis results, showing that the self-concept have a significant influence on the purchase intention a branded product. The effect from self-concept by 5.9%, so there are 94.1% other factors that influence could factors are environmental influences and the value of a product. Therefore, it is advisable for adolescence to be more responsible and wise before deciding to purchase a product. In addition, parents are also expected to be able to monitor and restrict children spending. Keywords: Self-Concept, Purchase Intention, Adolescence